Salmonella-induced pericarditis - Suranadi, I Wayan; Adnyana, I Komang Putra; Tarini, Ni Made Adi (The Journal of Infection in Developing Countries, 2025)
Introduction: Salmonella-induced pericarditis (SIP) is a rare complication of Salmonella infection, with only 30 cases reported to date, and a mortality rate of 14.8%. It is mostly associated with immunosuppression and can result in complications such as pericardial effusion, cardiac tamponade, and myopericarditis. Case Presentation: A 58-year-old man complained of chest pain, cold sweats, shortness of breath, cough, and a history of fever. Physical and supporting examinations including echocardiography and pericardial fluid culture were positive for Salmonella based on VITEK 2 Biomerieux. Based on antibiotic sensitivity testing for therapy selection, the patient received 2 grams of ceftriaxone via intravenous (IV) every 24 hours which was then maximized to 2 grams every 12 hours. Outpatient management was planned after confirming the amount of pericardial fluid, last culture results, and clinical improvement. Discussion: SIP is very rare. These infections are caused by direct spread from intrathoracic foci or hematogenous spread from other sites of infection, including cross-reactivity of infectious antigens with the body`s antigens, and/or the presence of infection stimulating host immune reactions. Antimicrobials such as fluoroquinolones and third-generation cephalosporins can be given for 4-6 weeks, especially in immunocompromised individuals or those with spread to extra-intestinal sites. Conclusions: SIP in adult patients with comorbidities and immunocompromised are associated with high morbidity and mortality. Early diagnosis, rational antibiotic therapy, and appropriate surgery provide good prognosis for patients.